Apakah Kualitas Audit Memperlemah Multinasionalitas dan Suaka Pajak dengan Penghindaran Pajak? - Benita Minggus Igakartika; Eko Ganis Sukoharsono; Mohamad Khoiru Rusydi (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to analyze the impact of multinationality and tax havens, with audit quality serving as a moderating variable. Methodology/approach: The population of this study consists of companies listed on the IDX80 index. Sample selection was conducted using purposive sampling methods, resulting in 215 observations. This research utilizes secondary data, which was analyzed using SPSS software. Findings: The findings indicate that both multinationality and tax havens positively influence tax avoidance. Audit quality is capable of mitigating the effect of multinationality and tax havens on tax avoidance. High-quality auditors can prevent tax avoidance practices in multinational companies and those utilizing tax havens through rigorous oversight and transparent financial reporting. Practical and Theoretical contribution/Originality: This study contributes to the existing theoretical framework by elucidating Jensen and Meckling's agency theory (1976) within the context of the observed phenomena. It also provides practical guidance for multinational corporations and tax haven users on how to reduce tax avoidance practices. Research Limitation: The independent variables used in this study do not fully explain tax avoidance behavior. Future researchers are encouraged to explore and incorporate other variables that may influence tax avoidance.